(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the professional development of future sports managers, emphasizing not only their organizational and economic knowledge but also the evolving profile of the modern sports manager. The study identifies key factors such as psychological resilience, stress tolerance, communicative competence, and decision-making ability, as well as interest in physical education and sports, through a specially designed questionnaire. The capabilities of prospective sports managers were assessed using this instrument. The results of the survey were analyzed within the cohort of students specializing in sports management. Differences between indicators were calculated using mathematical and statistical methods. By modifying the professional profile of a sports manager, the article highlights the essential professional and practical characteristics required in the field.